Functional analysis of root-preferential oil palm metallothionein promoter in tobacco - Masura, Subhi Siti; Shaharuddin, Noor Azmi; Masani, Mat Yunus Abdul; Chan, Kuang-Lim; Low, Eng-Ti Leslie; Chan, Pek-Lan; Rahmah, Abdul Rahman Siti; Amiruddin, Nadzirah; Abdullah, Mohd Puad; Azzeme, Azzreena Mohamad; Parveez, Ghulam Kadir Ahmad; Abd Rasid, Omar (Springer Science and Business Media Deutschland GmbH, 2024)
Root-specific or preferential promoters are essential to genetically modify plants with beneficial root traits. We have characterised the promoter from an oil palm metallothionein gene (EgMT) and performed a serial 5' deletion analysis to identify the region(s) essential for transgenes expression in roots. Stable functional characterisation of tobacco transgenic lines using the T1 generation showed that a deletion construct, designated as RSP-2D (1107 bp), directed strong GUS expression at all stages of root development, particularly in mature roots. Other constructs, RSP-2A (2481 bp) and RSP-2C (1639 bp), drove GUS expression in roots with an intensity lower than RSP-2D. The promoter activity was also detectable in seed pods and immature seeds, albeit at lower levels than CaMV35S. The promoter activity may also be induced by wounding as intact GUS staining was observed at the flower- and leaf-cutting sites of T1 samples carrying either RSP-2C or RSP-2D constructs. The promoter sequence contains cis-acting elements that may act as negative regulators and be responsible for root specificity. The results further indicated that the 5' UTR and ATATT sequences are essential for strong promoter activity. This study highlights the potential of RSP-2D promoter as a tool for modifying root traits through genetic engineering.